Intermittent Vision and Goal-Directed Movement: A Review. Issue 4 (14th May 2021) - Elliott, Digby; Bennett, Simon J.
Abstract: It is well known that vision makes an important contribution to the control of goal-directed movements. However, task performance can be maintained when vision is interrupted, such as when a goalkeeper faces a free kick in soccer and the ball moves behind teammates and opposing players. To maintain behavior, it is necessary to process the visual information available from intermittent samples. In this review, we consider the performance and learning effects of intermittent vision in tasks such as aiming, reaching and grasping, goal-directed locomotion and ball-catching. We review research that finds both interocular and intraocular integration contribute to continuous upper limb control with intermittent visual pickup/sampling. Recent work using intermittent visual presentation (i.e., stroboscopic vision) to facilitate learning of general and task-specific visual-motor skills indicates that training/learning protocols that challenge, but don't alter, the visual-motor processing associated with a specific visual-motor task can be effective. In this theoretical context, we discuss methodological and design factors that could impact the effectiveness of future training studies.